2011
DOI: 10.1007/s00421-011-2146-2
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and coverage effects of sporting compression garments on cardiovascular function, thermoregulatory function, and exercise performance

Abstract: Sporting compression garments (CG) are used widely during exercise despite little evidence of benefits. The purpose of this study was to investigate coverage and pressure effects of full-body CG on cardiovascular and thermoregulatory function at rest and during prolonged exercise, and on exercise performance. Twelve recreationally trained male cyclists [mean (SD) age, 26 (7) years; VO(2 max), 53 (8) mL kg(-1) min(-1)] completed three sessions (counterbalanced order), wearing either correctly-sized CG (CSG; 11-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
70
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(79 citation statements)
references
References 42 publications
6
70
3
Order By: Relevance
“…Higher skin temperature under the compression garments but identically increased core temperature was recorded in our study as well as other studies [2, 11, 21, 37]. Faster and greater rise of skin temperature has also been reported under compression garments during a warm-up [25].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Higher skin temperature under the compression garments but identically increased core temperature was recorded in our study as well as other studies [2, 11, 21, 37]. Faster and greater rise of skin temperature has also been reported under compression garments during a warm-up [25].…”
Section: Discussionsupporting
confidence: 89%
“…Although lower body compression garments alleviated orthostatic stress after the exercise in orthostatically intolerant athletes [5], no effect on cardiovascular response to orthostatic stress after exercise in normal females was detected in our study, and it has been shown recently that even whole body compression garments do not change cardiovascular function during orthostatic test at rest [21]. By means of near-infrared spectroscopy Agu et al [1] reported an increase in leg muscles oxygenation in patients with venous insufficiency when wearing the compression stockings, while our study has not disclosed any benefits of compression breeches on calf muscle oxygenation in healthy females in response to running training session.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Considering that sustained external pressure while wearing CG attenuates mechanical stress by reducing muscle oscillation [17], the use of CG during exercise might attenuate increases in muscle damage markers and inflammatory cytokines. Another mechanism underlying effectiveness of wearing CG may be improved venous return, resulting from assisted muscle pump action by the garments [18]. The augmented muscle pump action by wearing CG would be more advantageous when exercise intensity is relatively lower, because muscle pump action is dependent on exercise intensity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, positive effect of wearing CG is suggested to be observed during prolonged exercise with accumulated fatigue [1]. However, most of these previous studies have focused on the effectiveness of wearing CG on cardiovascular and metabolic variables during maximal or intensive endurance exercise lasting less than 60 min [1,3,7,12,13,1820]. Therefore, little information is available on whether wearing CG during prolonged running (> 60 min) affects exercise-induced changes in muscle damage markers and the inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%